2017
DOI: 10.1055/s-0043-106443
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal and Advanced Glycation End Products in Patients with Diabetes – What We Know so Far and the Missing Links

Abstract: Hyperglycemia explains the development of late diabetic complications in patients with diabetes type 1 and type 2 only partially. Most therapeutic efforts relying on intensive glucose control failed to decrease the absolute risk for complications by more than 10%, especially in patients with diabetes type 2. Therefore, alternative pathophysiological pathways have to be examined, in order to develop more individualized treatment options for patients with diabetes in the future. One such pathway might be the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 69 publications
5
38
0
2
Order By: Relevance
“…Protein-bound and free AGEs have been shown to be significantly elevated in experimental models of diabetes and in diabetic patients [6], [7], [8], [9], in parallel with their precursors [10], [11]. Studies have also shown that there is an association between AGEs and diabetic micro- and macrovascular complications (Reviewed in [12]), an association which is independent of HbA 1c . The reasons for this discrepancy may be due to the loss of detoxification capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Protein-bound and free AGEs have been shown to be significantly elevated in experimental models of diabetes and in diabetic patients [6], [7], [8], [9], in parallel with their precursors [10], [11]. Studies have also shown that there is an association between AGEs and diabetic micro- and macrovascular complications (Reviewed in [12]), an association which is independent of HbA 1c . The reasons for this discrepancy may be due to the loss of detoxification capacity.…”
Section: Introductionmentioning
confidence: 99%
“…A késői glikációs végtermékek -elsősorban az oxidatív stressz fokozódása révén -nagyban hozzájárulnak az érelmeszesedéshez és ezáltal a macrovascularis szövődmények kialakulásához [44]. Ezen túlmenően az AGE termékek kiemelkedő jelentőséggel bírnak a microvascularis szövődmények patomechanizmusában [45,46], amelyek közül a diabeteses nephropathiának szintén szerepet tulajdonítanak a szív-és érrendszeri betegségek kialakulásában [47]. A metforminkezelés igazoltan csökkenti mind a reaktív metabolitok, mind a következményes AGE termékek képződését [48][49][50].…”
Section: Megbeszélésunclassified
“…In den aktuellen Hypothesen geht man ebenfalls von oxidativem Stress, erhöhter ROS-Produktion und inflammatorischer Hyperaktivierung aus. Diese werden vor allem durch reaktive Metabolite, Advanced Glycation Endproducts (AGE) und gestörte Fettsäureoxidation hervorgerufen [27][28][29]. Diese Mechanismen verursachen ähnlich wie bei der Lungenfibrose vaskuläre Mikroläsionen, die über Endotheldysfunktionen und Apoptose zu Gerinnungsaktivierung, Chemokinfreisetzung und Kollagensynthese führen [28].…”
Section: Epidemiologie Und Pathophysiologieunclassified